PENDAMPINGAN PEMBUATAN ARUS KAS SEDERHANA PADA KONVEKSI IBU SEMI DI POLOKARTO JAWA TENGAH (SUPPORT TO CREATE SIMPLE CASH FLOW IN CONVECTION IBU SEMI DI POLOKARTO JAWA TENGAH) - Susanti, Ari; Trianita Saputra, Era; Octavia, Dewi Ika; Adyaksana, Rahandhika Ivan; Istiyanto, Budi (Jurnal Berdaya Mandiri, 2024)
The rapid development of MSMEs is not matched by the responsive attitude of MSME leaders. One of the problems faced by MSMEs is MSME Partner Konveksi Ibu Semi, where in terms of financial management, these MSMEs do not implement continuous recording of money inflows and outflows. This problem requires a strategy in the form of financial management assistance, including recording business cash flow and better separating personal and business finances. The method used is Action Research by providing understanding and training in the simple recording of cash flows using Excel. The steps performed include 1) the preparation step; 2) Implementation of service activities; 3) Evaluation and closure phase; 4) Comments. The results of this service are: 1) Partners can systematically apply simple cash flow recording and separate personal and business finances. 2) Partners are very enthusiastic and feel helped by the training on simple cash flow recording, as partners feel the benefits of being able to minimize. financial management errors; 3) Creating sound and clear corporate financial management, as we have consistently well implemented simple cash registers. Keywords: Convection MSME, Finance, Cash Flow